The Latarjet Procedure at the National Football League Scouting Combine: An Imaging and Performance Analysis. Issue 9 (31st August 2017) - LeBus, George F.; Chahla, Jorge; Sanchez, George; Akamefula, Ramesses; Moatshe, Gilbert; Phocas, Alexandra; Price, Mark D.; Whalen, James M.; LaPrade, Robert F.; Provencher, Matthew T.
Background: The Latarjet procedure is commonly performed in the setting of glenoid bone loss for treatment of recurrent anterior shoulder instability; however, little is known regarding the outcomes of this procedure in elite American football players. Purpose: (1) Determine the prevalence, clinical features, and imaging findings of elite college football athletes who present to the National Football League (NFL) Combine with a previous Latarjet procedure and (2) describe these athletes' performance in the NFL in terms of draft status and initial playing time. Study Design: Case series; Level of evidence, 4. Methods: After review of all football players who participated in the NFL Combine from 2009 to 2016, any player with a previous Latarjet procedure was included in this study. Medical records, position on the field, and draft position were recorded for each player. In addition, imaging studies were reviewed to determine fixation type, hardware complications, and status of the bone block. For those players who were ultimately drafted, performance was assessed based on games played and started, total snaps, and percentage of eligible snaps in which the player participated during his rookie season. Results: Overall, 13 of 2617 (<1%) players at the combine were identified with a previous Latarjet procedure. Radiographically, 8 of 13 (61%) showed 2-screw fixation, while 5 of 13 (39%) had 1 screw. Of the 13 players, 6 (46%) players demonstrated hardware complications. All players had evidence of degenerative changes on plain radiographs, with 10 (77%) graded as mild, 1 (8%) as moderate, and 2 (15%) as severe according to the Samilson Prieto classification. Six of the 13 (46%) players went undrafted, while the remaining 7 (54%) were drafted; however, no player participated in more than half of the plays for which he was eligible during his rookie season. Conclusion: Only a small percentage of players at the NFL Combine (<1%) had undergone a Latarjet procedure. High rates of postoperative complications and radiographically confirmed degenerative change were observed. Athletes who had undergone a Latarjet procedure demonstrated a variable amount of playing time, but none participated in more than half of their eligible plays during their rookie season.